2004
DOI: 10.1177/107110070402500503
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Shock Wave Therapy for the Treatment of Plantar Fasciitis

Abstract: One hundred fifty patients were enrolled in a multicenter, randomized, placebo-controlled, prospective, double-blind study to assess the clinical safety and effectiveness of extracorporeal shock wave therapy (ESWT) using the Dornier Epos Ultra for the treatment of plantar fasciitis. The Active Group was treated with electromagnetically generated shocks using ultrasound guidance during a single therapy session. The Control Group received a sham treatment under similar clinical conditions. The groups were demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0
11

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(80 citation statements)
references
References 32 publications
(40 reference statements)
3
66
0
11
Order By: Relevance
“…Many, but not all, randomized, blinded and controlled multicenter trials have demonstrated that ESWT is more effective than placebo treatment [18,24,34]. However, some studies showed disappointing results [6,13,33].…”
Section: Discussionmentioning
confidence: 99%
“…Many, but not all, randomized, blinded and controlled multicenter trials have demonstrated that ESWT is more effective than placebo treatment [18,24,34]. However, some studies showed disappointing results [6,13,33].…”
Section: Discussionmentioning
confidence: 99%
“…Extracorporeal shock wave therapy (ESWT) has been proposed as a potential method of treating patients with chronic disease without the need to stop weightbearing [10,16,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Many placebo-controlled clinical studies have been published reporting that ESWT is a successful treatment in the treatment of plantar fasciitis with success rates reaching 94% [5,[10][11][12][13][14][15][16][17]19,20]. However, some researchers have reported that ESWT showed no difference in effect from a placebo in the treatment of plantar fasciitis [6,[21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…There have been many studies evaluating the efficacy of ESWT in the treatment of plantar fasciitis and although the majority of these studies have reported effective and successful results [5,7,[9][10][11][12][13][14][15][16][17][18][19][20], some researchers have stated that ESWT has had no effect [6,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%